2011
DOI: 10.2500/ajra.2011.25.3614
|View full text |Cite
|
Sign up to set email alerts
|

Inherent Differences in Nasal and Tracheal Ciliary Function in Response to Pseudomonas aeruginosa Challenge

Abstract: Using primary murine nasal and tracheal airway cultures we show inherent differences in cilia function and increased susceptibility of the upper airway to attachment by Pseudomonas. Understanding the differences between upper and subglottic airway mucociliary clearance should lead to novel approaches in the management of upper airway infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 30 publications
0
17
0
1
Order By: Relevance
“…Studies have shown that CF patients with persistent P. aeruginosa in the sinuses often have a distinct lack of systemic antibody responses, thus questioning the current definition of chronic infection 12,26,27 . In addition to the altered immune response in these different niches, ciliary beat frequency has also been found to be altered in nasal airway cultures leading to significantly more P. aeruginosa attaching to these cultures than tracheal airway cultures 28 , therefore showing that mucociliary clearance is not uniform throughout the respiratory tract and may contribute to persistence in the upper reaches of the airways. Ciliary function is further impaired in CF patients and this may contribute to the unique susceptibility of CF patients to chronic P. aeruginosa infections.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that CF patients with persistent P. aeruginosa in the sinuses often have a distinct lack of systemic antibody responses, thus questioning the current definition of chronic infection 12,26,27 . In addition to the altered immune response in these different niches, ciliary beat frequency has also been found to be altered in nasal airway cultures leading to significantly more P. aeruginosa attaching to these cultures than tracheal airway cultures 28 , therefore showing that mucociliary clearance is not uniform throughout the respiratory tract and may contribute to persistence in the upper reaches of the airways. Ciliary function is further impaired in CF patients and this may contribute to the unique susceptibility of CF patients to chronic P. aeruginosa infections.…”
Section: Discussionmentioning
confidence: 99%
“…Ciliary activity accelerates in response to a variety of mechanical, [27][28][29] chemical, 30,31 hormonal, [32][33][34] pH, 35 and thermal stimuli (Table 1). 36,37 Extracellular nucleotides (adenosine and uridine) are especially potent regulators of epithelial functions stimulating mucociliary clearance through mucus secretion, increasing CBF, and gating ion channels involved in the maintenance of epithelial surface liquid volume.…”
Section: Dynamic Regulationmentioning
confidence: 99%
“…Recently, conditioned media from P. aeruginosa has been shown in vitro not only to depress basal CBF, but also to inhibit rapidly the ability of sinonasal cilia to respond to mechanical stimulation thereby neutralizing the ability of the respiratory epithelium to accelerate mucus clearance in response to infection. 29 H. influenzae, another common respiratory pathogen, has been shown to produce ciliotoxic substances that facilitate the bacteria's colonization of respiratory epithelium. H. influenzae produces lipooligosaccharide and protein D, which have been shown to cause stasis and destruction of cilia and ciliated cells, although the specific mechanisms of these toxins remains unclear.…”
Section: Microbial Factorsmentioning
confidence: 99%
“…19,20,43,44,46,48 Images of beating cilia from mature cultures were visualized by using a ϫ20 objective on an inverted microscope (DM IL; Leica Microsystems, Inc., Wetzlar, Germany) with a model A602f Basler area scan high-speed monochromatic digital video camera (Basler, AG, Ahrensburg, Germany) at 100 frames/s. Video images were analyzed with the Sisson-Ammons Video Analysis (SAVA) system version 2.1 (Ammons Engineering, Clio, MI).…”
Section: High-speed Digital Imaging Of Ciliary Beat Frequencymentioning
confidence: 99%